Improving Science Learning Outcomes through the Use of Torso Teaching Aids for SDN Pajang IV Students - Intan Agustina (Universitas Sebelas Maret, 2022)
Science learning outcomes about human limb bones in 5th grade students SDN Pajang IV are still lacking. Based on this case, the teacher takes action so that student learning outcomes can increase, by using torso. The purpose of this study was to improve student learning outcomes in the science subject about the bones of the human limbs which was carried out with 2 cycles of class action research. The results showed an increase in science learning outcomes. Student completeness reached 65% in improvement cycle 1 and reached 100% in improvement cycle 2. By using torso can improve science learning outcomes, because through the use torso as learning media, students are more interested and enthusiastic in participating in learning activities. So that students more easily understand the subject matter, do not get bored in learning, and easier to remember the material that has been studied.